Microvascular injuries, secondary edema, and inconsistencies in lung vascularization between affected and nonaffected pulmonary segments of non-critically ill hospitalized COVID-19 patients presenting with clinical deterioration. (April 2022) - Maincent, Cécile; Perrin, Christophe; Chironi, Gilles; Baqué-Juston, Marie.; Berthier, Frédéric; Paulmier, Benoît; Hugonnet, Florent; Dittlot, Claire; Farhad, Ryan Lukas.; Renvoise, Julien; Serrano, Benjamin; Nataf, Valérie; et al.
Purpose: We aimed to better understand the pathophysiology of SARS-CoV-2 pneumonia in non-critically ill hospitalized patients secondarily presenting with clinical deterioration and increase in oxygen requirement without any identified worsening factors. Methods: We consecutively enrolled patients without clinical or biological evidence for superinfection, without left ventricular dysfunction and for whom a pulmonary embolism was discarded by computed tomography (CT) pulmonary angiography. We investigated lung ventilation and perfusion (LVP) by LVP scintigraphy, and, 24 h later, left and right ventricular function by Tc-99m-labeled albumin-gated blood-pool scintigraphy with late (60 mn) tomographic albumin images on the lungs to evaluate lung albumin retention that could indicate microvascular injuries with secondary edema. Results: We included 20 patients with confirmed SARS-CoV-2 pneumonia. All had CT evidence of organizing pneumonia and normal left ventricular ejection fraction. No patient demonstrated preserved ventilation with perfusion defect (mismatch), which may discard a distal lung thrombosis. Patterns of ventilation and perfusion were heterogeneous in seven patients (35%) with healthy lung segments presenting a relative paradoxical hypoperfusion and hypoventilation compared with segments with organizing pneumonia presenting a relative enhancement in perfusion and preserved ventilation. Lung albumin retention in area of organizing pneumonia was observed in 12 patients (60%), indicating microvascular injuries, increase in vessel permeability, and secondary edema. Conclusion: In hospitalized non-critically ill patients without evidence of superinfection, pulmonary embolism, or cardiac dysfunction, various types of damage may contribute to clinical deterioration including microvascular injuries and secondary edema, inconsistencies in lung segments vascularization suggesting a dysregulation of the balance in perfusion between segments affected by COVID-19 and others. Summary Statement: Microvascular injuries and dysregulation of the balance in perfusion between segments affected by COVID-19 and others are present in non-critically ill patients without other known aggravating factors. Key Results: In non-critically ill patients without evidence of superinfection, pulmonary embolism, macroscopic distal thrombosis or cardiac dysfunction, various types of damage may contribute to clinical deterioration including 1/ microvascular injuries and secondary edema, 2/ inconsistencies in lung segments vascularization with hypervascularization of consolidated segments contrasting with hypoperfusion of not affected segments, suggesting a dysregulation of the balance in perfusion between segments affected by COVID-19 and others.